2005
DOI: 10.1074/jbc.m412793200
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Down-regulates Human OGG1 through Suppression of Sp1 Activity

Abstract: Cadmium is a well known human and animal carcinogen and is a ubiquitous contaminant in the environment. Although the carcinogenic mechanism of cadmium is a multifactorial process, oxidative DNA damage is believed to be of prime importance. In particular, cadmium suppresses the capacity of cells to repair oxidative DNA damage. In this study, cadmium treatment led to a significant increase in ␥-ray-induced 8-oxoguanine (8-oxoG) formation. Western blotting and semiquantitative reverse transcription-PCR revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 74 publications
4
39
1
Order By: Relevance
“…of the main DNA glycosylase activity responsible for the initiation of the base excision repair of 8-oxoguanine, an abundant and mutagenic form of oxidized guanine. The study of Bravard et al (2010) confirms that part of the inhibitory effect of low dose cadmium on the cellular 8-oxoguanine DNA glycosylase activity can be attributed to an already described reduced hOGG1 transcription (Youn et al, 2005). This moderate inhibitory effect of cadmium on hOGG1 mRNA levels cannot explain the d r a m a t i c d e c r e a s e o b s e r v e d i n t h e l e v e l s a n d a c t i v i t y o f h O G G 1 p r o t e i n .…”
Section: Cadmiumsupporting
confidence: 52%
“…of the main DNA glycosylase activity responsible for the initiation of the base excision repair of 8-oxoguanine, an abundant and mutagenic form of oxidized guanine. The study of Bravard et al (2010) confirms that part of the inhibitory effect of low dose cadmium on the cellular 8-oxoguanine DNA glycosylase activity can be attributed to an already described reduced hOGG1 transcription (Youn et al, 2005). This moderate inhibitory effect of cadmium on hOGG1 mRNA levels cannot explain the d r a m a t i c d e c r e a s e o b s e r v e d i n t h e l e v e l s a n d a c t i v i t y o f h O G G 1 p r o t e i n .…”
Section: Cadmiumsupporting
confidence: 52%
“…Here we show that the oxidative stress induced by a short exposure of human cells to a toxic concentration of cadmium results in nearly complete but reversible inactivation of the 8-oxoG DNA glycosylase activity of hOGG1. Chronic exposure to low doses of cadmium lowers the cellular activity of OGG1 in animal models (36,37) or in human cells (47). In the former cases, the cadmium-induced reduction of OGG1 activity was paralleled by lower enzyme levels most likely resulting from inhibition of gene expression at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…However, at present little is known concerning the effect of cadmium on the human OGG1 (hOGG1) protein activity. Only one study recently addressed this question, demonstrating that several hours' exposure of human cells to low cadmium doses reduced hOGG1 activity through a decrease in the hOGG1 gene expression at the transcriptional level (47). The present study aimed at establishing whether an acute exposure of human cells to a high cadmium concentration alters the 8-oxoG DNA glycosylase activity of hOGG1 and at clarifying the underlying mechanisms of Cd genotoxicity.…”
mentioning
confidence: 99%
“…On the other hand, another possible mechanism for the inhibition of OGG1 activity was suggested by other groups. Recently, Youn et al reported that the cadmium-mediated decrease in hOGG1 transcription was the result of decreased binding of the transcription factor Sp1 to the hOGG1 promoter (28). Whether the same mechanism also occurs in arsenic compound-treated cells or animals remains unknown.…”
Section: Discussionmentioning
confidence: 99%